Pengaruh Penggunaan Model Pembelajaran Kooperatif Berbantuan Permainan Sciwallplay terhadap Motivasi Belajar Siswa Kelas III di SDN 44 Ampenan - Urvi Azizah; Siti Istiningsih; Aisa Nikmah Rahmatih (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The use of conventional learning models (teacher-centered) which is still dominant and the minimal use of interactive digital media causes the learning motivation of class III students at SDN 44 Ampenan to be relatively low. This study aimed to determine the effect of using a cooperative learning model assisted by Sciwallplay Games on the learning motivation of third-grade students at SDN 44 Ampenan. The research employed a quasi-experimental method with a non-equivalent pretest-posttest control group design. The sample was selected using purposive sampling, involving 51 students of SDN 44 Ampenan, consisting of 25 students from Class III B (experimental group) and 26 students from Class III A (control group). Data were collected using a questionnaire to measure students' learning motivation. The results of the two independent sample t-test on the learning motivation questionnaire showed a significance value of 0.024, then Sig. (2-tailed) < 0.05 so it can be concluded that the use of the cooperative learning model assisted by Sciwallplay Games has a positive effect on increasing the learning motivation of third-grade students at SDN 44 Ampenan, which is shown through increased student activity, interest, and enthusiasm in participating in learning.